PERBANDINGAN KADAR PROFIL LIPID DARAH PADA STROKE ISKEMIK DAN STROKE HEMORAGIK DI RSUD DR. H. ABDOEL MOELOEK BANDAR LAMPUNG TAHUN 2014 - Zulhafis Mandala (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2015)
Background: Stroke is a disorder of brain function as well as global focal sudden and acute that occurred morethan 24 hours, due to interruption of blood flow to the brain. One risk factor for stroke is dyslipidemia. Blood lipids consist ofblood cholesterol levels, LDL (Low Density Lipoprotein), the levels of HDL (High Density Lipoprotein), and triglyceride levels.Purpose: To determine the ratio of blood lipid profile levels in ischemic stroke and hemorrhagic stroke at HospitalDr. H. Abdul Moeloek Bandar Lampung.Results: The prevalence of most types of stroke is ischemic stroke 73%. In ischemic stroke high cholesterol levelsby 62.4%, low HDL levels by 51.2%, high LDL levels by 57.6%, the levels of high triglyceride levels by 53.6%. While inhemorrhagic stroke high cholesterol levels by 40.9%, low HDL levels by 44.0%, high LDL levels by 43.2%, the levels of hightriglyceride levels by 53.6%.Conclusion: Increased levels of cholesterol, LDL and HDL levels decrease more significantly in ischemic strokecompared with hemorrhagic stroke. Whereas triglyceride levels obtained comparable results between ischemic stroke andhemorrhagic stroke.